Evolutionary job scheduling with optimized population by deep reinforcement learning. Issue 3 (4th March 2023) - Zeng, Detian; Zhan, Jun; Peng, Wei; Zeng, Zengri
Abstract : The sorting operation of the production line in a heavy industrial scenario has the double complexity of the problem and the data. To improve production efficiency, the operation needs to be optimized. Aimed at this problem, this article designs a data representation method and an evolutionary job scheduling algorithm with an optimized population by deep reinforcement learning (DRL). Moreover, a real industrial dataset is contributed. The representation method represents the job data by referring to the bag-of-words model. The evolutionary algorithm uses DRL to initialize the genetic algorithm (GA)'s population and further evolves the population through the GA to obtain the final scheduling result. The experimental results indicate that the evolutionary algorithm has achieved the largest decrease in the average times for frame clearing on the real and simulated validation datasets, which are 12.54 % and 11.43 %, respectively. It is of great significance for subsequent scheduling of the full-scenario digital twin.